The Influence Of Internal Control Systems And The Competence Of Bumdes Management Apparatus On The Accountability Of Village Fund Management In Pondok Kelapa Village, Pondok Kelapa District, Central Bengkulu Regency - Redha Amalia; Ahmad Soleh; Herlin Herlin (Universitas Dehasen Bengkulu, 2026)
The aim of this research is to determine the simultaneous effect of the internal control system and the competence of the village-owned enterprise (BUMDes) management apparatus on the accountability of village fund management in Pondok Kelapa, Pondok Kelapa District, Central Bengkulu Regency. The data collection method in this study used a questionnaire technique, with a sample of 79 respondents. The results of the study show that the multiple linear regression is Y = -2.102 + 0.324 X1 + 0.727 X2 + 1.478. The results indicate that the Internal Control System (X1) test shows t-count 2.593 > t-table 1.665 and significance 0.011 < 0.05, meaning the Ha hypothesis is accepted and the Ho hypothesis is rejected. This means that the Internal Control System (X1) has a positive and significant effect on the Accountability of Village Fund Management (Y) in Pondok Kelapa, Pondok Kelapa District, Central Bengkulu Regency. The Competence of BUMDes Management Apparatus (X2) test shows t-count 6.890 > t-table 1.665 and significance 0.000 < 0.05, meaning the Ha hypothesis is accepted and the Ho hypothesis is rejected. The Competence of BUMDes Management Apparatus (X2) has a positive and significant effect on the Accountability of Village Fund Management (Y) in Pondok Kelapa, Pondok Kelapa District, Central Bengkulu Regency. Based on the comparison of F-count and F-table values, the F-count value is greater than the F-table value, i.e., 64.478 > 2.72, so it is concluded that the hypothesis is accepted. This means there is a simultaneous effect between the Internal Control System (X1) and the Competence of BUMDes Management Apparatus (X2) on the Accountability of Village Fund Management (Y) in Pondok Kelapa, Pondok Kelapa District, Central Bengkulu Regency. This is evident from the significance level of 0.000 < 0.05.